Oratorium Sancti Joannis Nepomuceni by Anton Neumann - Cermak, Marek (Musicologica Olomucensia, 2022)
Anton Neumann was a Czech German-language composer, active mainly in Moravia, Lower Palatinate, Austria and present-day Poland (Brno, Zweibrucken, Kromeriz, Krakow, Vienna, Olomouc). He was also a violin virtuoso and Kapellmeister whose artistic legacy and significance have not yet been sufficiently discovered and presented. Neumann's compositions are widely distributed in the music collections of Central and Western Europe. His Oratorium Sancti Joannis Nepomuceni is currently housed in the music archives of the Benedictine monastery in Lambach, where his numerous church and secular compositions have been preserved. Neumann's setting of a German libretto by an unknown author dates from the 1760s. The composer wrote the work in a style that is currently usually referred to as 'Sturm und Drang'. He renders the text in great detail with a varied palette of affects and musical-rhetorical figures. These figures often belong to the realm of acoustic symbolism. Combined with the contrasting and carefully crafted dynamics, Neumann's work has a very dramatic effect. The modern premiere of the work was staged in 2015 in Olomouc. The paper presents new information about the composer's life and artistic career, using the example of his Nepomuk Oratorio to present the peculiarities of his compositional style in the form of comments and musical examples.
Keywords: Oratorio; St John of Nepomuk; Anton Neumann; Lambach